A comparison of a new alcohol‐free 0.2% chlorhexidine oral rinse to an established 0.2% chlorhexidine rinse with alcohol for the control of dental plaque accumulation. Issue 4 (9th October 2015) - Papaioannou, W; Vassilopoulos, S; Vrotsos, I; Margaritis, V; Panis, V
Abstract: Objectives: To compare the clinical efficacy of two formulations (alcohol and alcohol free) of 0.2% chlorhexidine (CHX) rinses on plaque, gingivitis and discoloration of teeth. Methods: This double‐blind crossover study consisted of one group of 10 volunteer dental students that followed two 21‐day experimental gingivitis test periods. During these periods, the subjects abstained from oral hygiene except for the oral rinse provided. The study started after an initial two‐week preparation programme that included a professional prophylaxis and repeated oral hygiene instructions. This was repeated for the 14‐day washout period between the two rinses, including prophylaxis as per the first stage of the study. A calibrated examiner performed the clinical measurements at the beginning (baseline) and end of each study stage. The presence and amount of plaque were recorded using the Silness and Löe plaque index (PI) and gingival inflammation by the gingival index (GI) while the discoloration index (DI) was recorded on the buccal and lingual surfaces of the six anterior teeth of both the mandible and maxilla. Results: Mean PI increased similarly for both solutions; however, the differences between initial and final values were statistically significant only for CHLOREL ® . Similarly, the mean values for the GI showed small increases over the course of the study periods, but not statistically significant for either solution. The mean DI increased significantly for both solutions. Regarding the comparison of the initial and final values ​​between the solutions, per index, no statistically significant differences were observed. Conclusion: The non‐alcoholic chlorhexidine rinse had comparable levels of action as the generally recognized gold standard alcoholic rinse.